The effects of different dietary nutritional levels on meat quality, rumen microbiota, and muscle metabolomics in Tibetan Plateau yaks - Xu, Shengchun; Wang, Shuxiang; Zhang, Jiyuan; Wang, Xun; Yang, Yingkui; Li, Shengsheng; Xiang, Yang; Nie, Hongxin; Li, Yuming; Zeng, Ziming; Chai, Shatuo; Liu, Shujie (Frontiers in Microbiomes, 2025)
IntroductionThe nutritional level of the diet plays a crucial role in maintaining the balance of the yak rumen microbiota. To explore the relationship between dietary nutritional levels, the rumen microbiota, and muscle metabolites, we examined the characteristics of the yak rumen microbiota and muscle metabolome under different dietary nutritional levels.MethodsRandomly divide 24 yaks with similar body weights, [235.96 ± 12.46 kg], into three groups. These groups were subjected to three nutritional feeding levels: ad libitum feeding (AL), 70% of ad libitum intake (IR70), and 40% of ad libitum intake (IR40). When the yaks in the AL group gained 70 kg in body weight, they were slaughtered.ResultsThe results indicated that the ad libitum feeding group (AL) demonstrated superior edible meat quality in terms of Chroma L*, Chroma a*, and shear force, compared to the 70% intake group (IR70) and the 40% intake group (IR40). At the phylum level, the abundance of Patescibacteria was notably greater in the IR40 group compared to both the AL group and the IR70 group. At the genus level, the relative abundance of Succinimonas was higher in the AL group than in both the IR70 and IR40 groups. Untargeted metabolomics analysis revealed that the levels of metabolites such as 5-Methylcytosine, Cytosine, and Thymine were upregulated in the longissimus dorsi muscle of the AL group, which contributed to the enhancement of meat flavor. Furthermore, Spearman's correlation analysis revealed a notable relationship between the rumen microbiota and both meat quality and metabolite levels. pH45min is positively correlated with trans-Cinnamic acid. Methanobrevibacter exhibited a positive correlation with the concentration of 4-(Diethylamino)benzaldehyde, while Candidatus_Saccharimonas showed a positive correlation with the concentration of phenylacetylglycine.DiscussionThis study provides scientific evidence for understanding the impact of different nutritional feeding conditions on yak meat quality, rumen microbiota, and related muscle metabolomic pathways. It also reveals the potential impact of these factors on meat flavor. These findings offer important reference information for optimizing yak husbandry management, improving the formation of beef flavor compounds, and understanding their regulatory mechanisms.